Introduction: Kamal Hassan’s scholarly career and this festschrift - Hasan, Md. Mahmudul (IIUM Press, 2023)
My long acquaintance with Kamal Hassan and with his works testifies that he was an embodiment of integration of knowledge. In today’s world, most academics are specialists in certain areas of expertise. Various disciplines, such as the natural and social sciences as well as the humanities and religious sciences, are distant and scholars are field-specific. Most scholars who are knowledgeable about the humanities and social sciences are inadequately conversant with the religious sciences. Conversely, many with a thorough grasp of the religious sciences are far removed from the knowledge of the humanities and social sciences. In such a state of affairs, it was fascinating to see in Kamal Hassan a multifaceted scholar with remarkable insights of various subjects – a true embodiment of integration of knowledge. As the various sections of this book confirm, the plurality of his scholarship remained a source of inspiration for many, especially those in IIUM.